(untitled) (Pedagogy of Higher and Secondary Education, 2012)
У статті теоретично узагальнено психолого-педагогічну сутність самостійної навчальної діяльності студентів у процесі вивчення мистецьких дисциплін. Зазначено певні особливості мистецької творчої діяльності студентів. Ключові слова: самостійна навчальна діяльність, самостійність, мистецькі дисципліни, творча діяльність. The article reveals general pedagogical and psychological characteristics of independent training activities in the process of learning art disciplines. There is also mentioned some specific of the creative activities related to the art. Key words: independent training activities, independence, art disciplines, creative activities.